Bandgap widening in macroporous silicon photonic crystals by multiperiodic structures. (14th May 2018) - García, D Segura; Cardador, D; Vega, D; Santos, M; Dios, F; Rodriguez, A
Abstract: Large bandgaps with low transmission in 3D macroporous silicon photonic crystals have been proved as an interesting technology for the development of optical filters and spectroscopic MIR gas sensors. The aim of this study is the investigation of different bandgap widening methods based on multiperiodic structures for 3D macroporous silicon photonic crystals. To do so, chirped modulations and structures with different periodicity groups have been modelled and theoretically analysed by means of 3D FDTD simulations. They have revealed that by using different decreasing periodicity groups, bandgaps with null transmission and widths as high as 1800 nm, 4 times the original single periodicity photonic crystal bandgap, can be obtained. Furthermore, it has been shown that a resonant cavity with a 20% transmission can be placed in a 1 μ m wide bandgap. The results open a way to use this type of structures not only for gas sensing but also for other purposes such as wide stop-band filters, selective filters or broadband mirrors.